Ink Compositions for Printable Thermoelectric Materials

Through Cu-Se-S-based ink combination and printing and baking process, high-performance, environmentally friendly and stable flexible printing thermoelectric materials have been developed, solving the complex and cost-effective manufacturing process of traditional thermoelectric equipment and achieving efficient and economical thermoelectric performance.

JP7653189B2Active Publication Date: 2025-03-28KARLSRUHER INST FUR TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023569754
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-11
Filing Date
2022-05-05
Publication Date
2025-03-28
Estimated Expiration
2042-05-05

AI Technical Summary

Technical Problem

The prior art is difficult to develop high-performance, environmentally friendly and stable flexible printed thermoelectric materials, especially without pressure treatment, and the manufacturing process of traditional thermoelectric equipment is complex and costly.

Method used

Using Cu-Se-S-based ink combination, flexible thermoelectric materials are manufactured through printing and baking processes, and non-standard β-Cu2-δSe is used as an intrinsic binding agent to reduce the interference of particle boundaries on carrier transmission and improve thermoelectric performance.

Benefits of technology

It realizes efficient, environmentally friendly and stable flexible printing thermoelectric materials, with high thermoelectric power factor and ZT value, suitable for large-scale applications and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653189000003
    Figure 0007653189000003
  • Figure 0007653189000004
    Figure 0007653189000004
  • Figure 0007653189000005
    Figure 0007653189000005
Patent Text Reader

Abstract

The present invention relates to an ink composition comprising a precursor material for a thermoelectric material, a precursor material for an inorganic binder comprising a mixture of Cu powder, Se powder and optionally S powder, an organic solvent and an organic binder. The present invention also relates to a Cu-Se-S based ink composition for a printable thermoelectric material, comprising a mixture of Cu powder, Se powder and S powder. The present invention further relates to a flexible printed thermoelectric material obtained by printing the ink of the present invention. The present invention further relates to high power density flexible printed thermoelectric generators, heat flow sensors and thermoelectric coolers comprising flexible printed thermoelectric materials, and the use of said thermoelectric generators, heat flow sensors and thermoelectric coolers, especially in large scale applications. The present invention also relates to a method for producing a flexible printed thermoelectric material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ink composition for printable thermoelectric materials, comprising a precursor material for the thermoelectric material, a precursor material for an inorganic binder comprising a mixture of Cu powder, Se powder and optionally S powder, an organic solvent and an organic binder. The present invention also relates to a Cu-Se-S based ink composition for printable thermoelectric materials, comprising a mixture of Cu powder, Se powder and S powder, an organic solvent and an organic binder. The present invention further relates to a flexible printed thermoelectric material obtained by printing the ink of the present invention. The present invention further relates to a high power density flexible printed thermoelectric generator comprising a flexible printed thermoelectric material and the use of said thermoelectric generator, especially in large scale applications. The present invention also relates to a method for producing a flexible printed thermoelectric material.

[0002] The technical field of the present invention generally relates to printable thermoelectric materials, especially for large-scale applications. Thermoelectrics (TE) is a simple technology without moving elements that can be used to recover waste heat and convert it to electricity, detect heat flow (heat flow sensor) and control the local temperature of a system. Currently, about 65% of the consumed energy is wasted as heat, so converting waste heat to electricity with thermoelectric generators (TEGs) can greatly boost the renewable energy sector. Heat flow sensors are used to detect heat dissipation from insulation systems. They are also employed in battery applications and other electronic devices for safety measures such as monitoring heat dissipation from the system and explosion proofing the system. Thermoelectric coolers (TECs) have also been used to maintain local temperatures in various systems (e.g., microelectronic devices, sensitive chemicals). Unlike conventional bulk TE materials, high performance printable TE materials could provide 2D / 3D devices with low manufacturing costs, shape variety and high power output density.

[0003] Conventionally, most research on thermoelectric conversion has focused on the design of TE materials and their performance index ZT = (S 2Much of the research has focused on improving the ZT (σ / κ)·T (S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature). A higher ZT value indicates a better performance of the TE material. However, there has been little focus on developing cost-effective TE devices. Although many high-performance TE materials with ZT>1 have already been developed, it is still difficult to fabricate TE devices with high output power density at low cost using bulk materials due to the large amount of materials used in the manufacturing process. Moreover, the fabrication of such TE devices often relies on elaborate and time-consuming processes that require multiple steps. Moreover, TE devices made from bulk materials are generally cubic or other symmetrical shapes, which makes it difficult to integrate them into non-planar surfaces of various systems.

[0004] Printing techniques can be introduced to overcome the limitations associated with conventional TE devices. High-performance printable TE materials have the potential to provide low manufacturing costs, geometric diversity, and high output power density for rapid fabrication of TE devices for large-scale applications. However, it is challenging to design printed materials with ZT ≥ 1 while exhibiting good printability. The TE parameters of inorganic printed materials, especially σ, are affected during ink processing, resulting in low ZT. Organic-based materials are known to exhibit good printability, but they exhibit poor performance, mainly due to very low S. Also, the fabrication of efficient printed TE devices requires n-type and p-type printed materials with comparable performance. Among conventional TE materials, (SbBi) is commonly used for bulk TE devices. 2 Te 3 It is a material based on SbBi. 2 Te 3 It has been widely targeted that n-type and p-type bulk TE materials in the system be printable while maintaining high performance at room temperature. Unfortunately, the charge carrier transport at grain boundaries is disrupted by binders and additives, which leads to a decrease in the overall ZT.

[0005] Bi 0.4 Sb 1.6 Te3 The particles are bonded to the molten Te, resulting in Sb 2 Te 3 A ZT of about 1 has been achieved in printed thin films of Bi. However, processing requires intermediate high pressure treatment after printing. 2 Te 3 In thin films, the interface modification results in a ZT of approximately 0.2 and a maximum of 3.63 μW cm -1 K -2 A power factor value of 10 ... 2 Te 3 and Bi 0.5 Sb 1.5 Te 3 The flexible nanowire thin films of 1.80 μW cm2 and 1.90 μW cm2 were obtained by thermal annealing after printing. -1 K -2 and 1.10 μW cm -1 K -2 In other reports, a power factor of 1000 nm was achieved using p-type Sb 2 Te 3 ZT values ​​of 0.3 and 0.2 have been achieved in Sb-based thin films. 2 Te 3 -Bi using inorganic binder composed of ChaM solution 2 Te 3 It has also been reported that the ZT of the system's p-type and n-type spray-coated / 3D-printed TE thin films is about 1. However, the synthesis process is complicated and requires multiple steps. Another drawback is that all the above printed TE materials have poor flexibility.

[0006] Thus, there is still a lack of high performance, environmentally stable, flexible, printable TE materials for device applications that do not require pressure processing, mainly due to low σ or poor printability. (SbBi) 2 Te 3 The n-type and p-type materials in the series are known to exhibit good TE performance at room temperature, but have poor printability. Furthermore, the resistivity increases during ink processing, limiting their use in printing techniques. Therefore, it is necessary to develop new materials that have good printability, high power factors (S 2Thus, it has been a challenge to develop flexible, environmentally stable, and highly efficient inorganic TE materials with low thermal conductivity (κ) and low thermal conductivity (σ).

[0007] In view of the above, it is an object of the present invention to provide an environmentally stable and highly efficient inorganic printable TE material that can reproducibly and efficiently provide flexible TE devices with improved TE performance and high power density at low cost.

[0008] According to the present invention, the above object is achieved by providing an ink composition for printable thermoelectric materials having the features as set forth in claim 1. The above object is further achieved by providing a Cu-Se-S based ink composition for printable thermoelectric materials having the features as set forth in claim 7. The above object is also achieved by a method for producing a flexible printed thermoelectric material having the features as set forth in claim 8. Furthermore, the above object is achieved by a flexible printed thermoelectric material having the features as set forth in claim 12. Furthermore, the above object is achieved by providing a flexible printed thermoelectric generator having the features as set forth in claim 14 and its use having the features as set forth in claim 16. Preferred embodiments of the invention are set forth in the dependent claims.

[0009] The present invention is based on a novel strategy to fabricate flexible printed thermoelectric materials containing inorganic binders, which can be synthesized by the application of non-stoichiometric β-Cu through a simple printing-sintering process. 2-δ Se bridges the grains of the TE material, and thus, unlike conventional inorganic powder-based printed thin films that contain grain boundaries, the present invention minimizes the interruption of carrier transport at the grain boundaries caused by binders and additives, resulting in an advantageous high electrical conductivity σ and thus improved TE performance.

[0010] Specifically, the present invention provides an ink composition for printable thermoelectric materials, the ink composition comprising a precursor material for thermoelectric materials, a precursor material for an inorganic binder containing a mixture of Cu powder, Se powder and S powder, an organic binder, and an organic solvent, wherein the molar ratio of the Cu powder to the total of the Se powder and S powder is 2:1, and the molar ratio of the Se powder to the S powder represented by the formula (1-x)Se:xS is in the range of 0≦x≦0.20. Further, the weight ratio of the precursor material for thermoelectric materials to the precursor material for inorganic binders represented by [(1-y) thermoelectric materials: y inorganic binders] is in the range of 0<y≦0.25.

[0011] Preferably, the precursor material for thermoelectric materials is a precursor material for p-type thermoelectric materials, and preferably, it is a powder of a Bi-Sb-Te alloy in which the molar ratio of Te to the total of Bi and Sb is 3:2.

[0012] More preferably, the precursor material for thermoelectric materials is a powder of a Bi-Sb-Te alloy in which the molar ratio of Te powder, Bi powder and Sb powder is 3:0.5:1.5.

[0013] The ink composition according to the present invention may further contain at least one additive selected from siliceous or siliceous and / or aluminous materials, preferably fumed silica and / or liquid rheology dispersing additives.

[0014] The particle size of each of the Cu powder, Se powder and S powder is preferably 500 μm or less.

[0015] According to the present invention, the weight ratio of the precursor material for thermoelectric materials to the precursor material for inorganic binders represented by [(1-y) thermoelectric materials: y inorganic binders] is preferably in the range of 0.01≦y≦0.20, and more preferably in the range of 0.05≦y≦0.10.

[0016] The present invention further provides a Cu—Se—S-based ink composition for printable thermoelectric materials, the ink composition comprising a mixture of Cu powder, Se powder and S powder, an organic binder, and an organic solvent, wherein the molar ratio of the Cu powder to the total of the Se powder and S powder is 2:1, and the molar ratio of the Se powder to the S powder represented by formula (1-x)Se:xS is in the range of 0 < x ≦ 0.20.

[0017] Furthermore, the present invention provides a method for manufacturing a flexible printed thermoelectric material, comprising: - providing an ink composition according to the present invention; - printing the ink composition on a substrate; - sintering the ink composition at a temperature of 200° C. to 500° C. for at least 60 seconds. The method is provided.

[0018] The step of sintering the ink composition can be carried out by photonic flash sintering of the ink composition, and then, after sintering, the printed thin film is pressed.

[0019] Preferably, the step of providing the ink composition includes wet ball milling of a precursor material for a thermoelectric material, a precursor material for an inorganic binder, an organic binder, and an organic solvent.

[0020] The step of printing the ink composition on a substrate is preferably carried out by at least one selected from the group consisting of screen printing, doctor blade coating, airbrush coating, inkjet printing, and 3D printing.

[0021] In a further aspect, the present invention provides a flexible printed thermoelectric (TE) material obtained by printing an ink composition according to the present invention on a substrate and sintering the ink composition at a temperature of 200° C. to 500° C., wherein the printed thermoelectric material is Cu 2-δ S x Se 1-xphase, where 0≦x≦0.20 and 0≦δ≦0.15.

[0022] The flexible printed thermoelectric material preferably has a thickness of 10 to 250 μm.

[0023] The present invention further provides a flexible printed thermoelectric generator (printed TEG) comprising the aforementioned flexible printed thermoelectric material as a p-type leg.

[0024] According to a preferred embodiment, the flexible printed TEG further comprises an n-type leg fabricated from an Ag—Se based ink composition for n-type printable thermoelectric material.

[0025] The flexible printed TEGs described above can be used in heat flow sensor applications, waste heat recovery applications, or cooling applications when integrated with wearable materials to maintain or reduce body temperature.

[0026] According to the present invention, non-stoichiometric β-Cu alloys can be prepared through a simple printing-sintering process. 2-δ A 2D / 3D printable TE material with a high figure of merit at room temperature has been developed by bridging the grains of the TE material using a Se-based inorganic binder (IB). In particular, the present invention provides a very easy and fast method for producing the printable TE material without the need for a complex multi-step process. Furthermore, the printable TE material is highly reproducible, and the provided printed material is environmentally stable. The resulting flexible printed TE material surprisingly has a very high TE power factor and ZT at room temperature. By using the TE material of the present invention in the p-type leg, a flexible printed TE generator can be produced that exhibits a very high maximum output power density.

[0027] The present invention, including preferred embodiments thereof, will now be described in more detail with reference to the accompanying drawings. [Brief description of the drawings]

[0028] [Figure 1] (a) XRD patterns at room temperature of the thin film (1-y)BST-(y)IB with y = 0, y = 0.10, and y = 1. (b) XRD pattern and Rietveld refinement result of the thin film with y = 1 at room temperature. (c) Fourier map of the electron density distribution of Cu and Se atoms in the β-Cu2-δSe phase in each plane along the

[0001] direction. (d) Temperature-dependent XRD pattern of the thin film with y = 1. [Diagram 2] (a) Composition-dependent Seebeck coefficient of the printed thin film of Example 1 sintered at 623 K and 703 K. (b) Temperature-dependent Hall coefficient (RH), (c) Hall carrier concentration (ηH), and (d) Hall carrier mobility (μH) of the printed thin film of Example 1. [Diagram 3] Variation of thermoelectric parameters (a) S, (b) σ, and (c) κ at temperatures between 300 and 400 K for the thin films of Example 1. (d) Temperature-dependent power factor Sσ for all the thin films of Example 1. [Figure 4] Figure of merit for temperature dependence of the thin film of Example 1. [Diagram 5] (a) Output voltage and (b) output power variation of the printed TEG with current while operating at each ΔT. (c) ΔT-dependent open circuit voltage (Voc) and maximum power output (Pmax) of the printed TEG. [Figure 6] XRD diffraction patterns and Rietveld refinement results of Cu2Se1-xSx thin films at (a) x = 0 and (b) x = 0.1 in Example 2. [Figure 7] (a) Screen-printed thin film of Example 2 bent with a finger. (b) Resistance of the thin film at no stress R0 and change in resistance of the thin film with bending cycles. (c) Resistance of the thin film when bent and relaxed. [Figure 8] (a) Change in Seebeck coefficient S with ball milling time for each composition of 0≦x≦0.20 in Example 2. Temperature-dependent transport parameters of the printed thin film with x=0.10 for each ball milling time: (b) electrical conductivity σ, (c) hole carrier concentration pH, and (d) hole carrier mobility μH. [Figure 9]TE parameters of the temperature dependence of the printed thin films with x = 0 and 0.10 in Example 2: (a) Seebeck coefficient S, (b) electrical conductivity σ, (c) thermal conductivity κ, (d) power factor S2σ, and (e) figure of merit ZT. [Figure 10] Changes in (a) output voltage and (b) output power of the flexible TEG of Example 2 due to the current during operation at each ΔT. (c) Open circuit voltage (Voc) and maximum power output (Pmax) of the printed TEG as a function of ΔT. (d) Seebeck coefficient per thermocouple at each ΔT. [Figure 11] Flash-sintered (a) p-type 0.9(Bi0.5Sb1.5Te3)-0.1(IB) and (b) n-type 0.9(Bi2(SeTe)3)-0.1(IB) printed thin films. The inks were prepared by a wet ball process.

[0029] As described above, the present invention is based on a novel strategy for manufacturing a flexible printed thermoelectric material containing an inorganic binder, and the inorganic binder is non-stoichiometric β-Cu 2-δ Se bridges the crystal grains of the TE material through a simple printing-sintering process, thereby avoiding the interruption of carrier transport at the grain boundaries. According to the present invention, an ink composition containing a precursor material for a thermoelectric material, a precursor material for an inorganic binder containing a mixture of Cu powder, Se powder, and optionally S powder, an organic binder, and an organic solvent is used for the production of a printable TE material. The molar ratio of the total of Cu powder, Se powder, and S powder is 2:1. Further, the molar ratio of Se powder to S powder represented as (1 - x)Se:xS is in the range of 0 ≦ x ≦ 0.20. The amounts of the precursor material for the thermoelectric material and the precursor material for the inorganic binder are adjusted so that the weight ratio of the precursor material for the thermoelectric material to the precursor material for the inorganic binder represented as [(1 - y) thermoelectric material:y inorganic binder] is in the range of 0 < y ≦ 0.25.

[0030] That is, the S powder does not necessarily have to be contained in the precursor material for an inorganic binder, but can be contained as an optional element, and the molar ratio of the Se powder to the S powder represented by the formula (1-x)Se:xS is in the range of 0≦x≦0.20. In other words, the present invention includes an embodiment in which the precursor material for an inorganic binder is composed of a mixture of a Cu powder and a Se powder, and the molar ratio of the Cu powder to the Se powder is 2:1.

[0031] As will be described in more detail in the Examples below, when the weight ratio of the precursor material for the thermoelectric material to the precursor material for the inorganic binder in the ink composition is within the above range, the resulting printed TE material has an excellent power factor (S 2 It has been found that the non-stoichiometric β-Cu alloy has not only a high σ but also an excellent thermoelectric figure of merit (ZT) when the amount of inorganic binder is within the above range. 2-δ This is because Se bridges the grains of the TE material, preventing the interruption of carrier transport at the grain boundaries. On the other hand, when the amount of inorganic binder is y>0.25, β-Cu 2-δ The Se phase forms a percolation pathway, and the β-Cu phase 2-δ The thermal transport phenomenon is dominated by the Se phase.

[0032] In one particular embodiment, the amount of inorganic binder is such that the high temperature dependent power factor S 2 In terms of σ and a high figure of merit ZT, 0.05≦y≦0.10.

[0033] The thermoelectric precursor material contained in the ink of the present invention is not particularly limited, and any p-type or n-type inorganic material can be suitably applied. An example of a suitable material is Bi z Sb 2-z Te 3 , n-type Bi 2 (TeSe) 3 , n / p-type half-Heusler alloys, and n / p-type skutterudites. In a preferred embodiment, the precursor material for a thermoelectric material is a precursor material for a p-type thermoelectric material.

[0034] Generally, the precursor material for the thermoelectric material in the ink of the present invention includes powders of inorganic n-type or p-type materials. The precursor material for the thermoelectric material may be a powder of the thermoelectric material, or may include powders of elements that form the thermoelectric material during the treatment of the ink composition according to the present invention.

[0035] In particular, when the TE material is p-type Bi z Sb 2-z Te 3 where, the precursor material for the thermoelectric material contained in the ink of the present invention is a powder of a Bi-Sb-Te alloy in which the molar ratio of the sum of Te, Bi and Sb is 3:2. In a preferred embodiment, the thermoelectric material is p-type Bi 0.5 Sb 1.5 Te 3 and the corresponding precursor material is a powder of a Bi-Sb-Te alloy in which the molar ratio of Te, Bi and Sb is 3:0.5:1.5.

[0036] As described above, the inorganic binder incorporated in the ink of the present invention can contain sulfur. Surprisingly, it has been found that by substituting Se with S, the TE performance of flexible printed materials can be significantly improved. Furthermore, as shown in the examples described below, the flexibility and bending characteristics of the TE material obtained by using a Cu-Se-S-based material are greatly improved.

[0037] Therefore, the present invention also targets a printable Cu-Se-S-based ink composition for thermoelectric materials, the ink composition includes a mixture of Cu powder, Se powder and S powder, the molar ratio of the Cu powder to the sum of the Se powder and the S powder is 2:1, and the molar ratio of the Se powder to the S powder represented as (1 - x)Se:xS is in the range of 0 < x ≤ 0.20.

[0038] As outlined above, the ink composition according to the present invention further comprises an organic solvent and an organic binder, preferably polyvinylpyrrolidone (PVP), and may comprise at least one additive selected from a siliceous or aluminous material, preferably fumed silica, and / or a liquid rheological dispersion additive, preferably BYK430.

[0039] The organic binder is incorporated in the ink composition of the present invention as a film-forming additive. A suitable binder is easily soluble in organic solvents, allowing the formation of a scratch-resistant thin film, for example at room temperature. Furthermore, the binder must provide good stability to the dried thin film and ensure that no visible cracks are generated on the surface.

[0040] Suitable organic binders are acrylonitrile butadiene styrene (ABS), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polyvinylpyrrolidone (PVP) or polystyrene-based resins or corresponding copolymers thereof. Preferably, the organic binder is polyvinylpyrrolidone (PVP).

[0041] The organic binder may have a weight average molecular weight Mw of about 10,000 to 5,000,000 g / mol, preferably about 10,000 to 1,000,000 g / mol, and more preferably about 20,000 to 100,000 g / mol.

[0042] Organic binders are generally commercially available and the weight-average molecular weight Mw of the organic binder refers to the value specified in the manufacturer's data. If these data are not available, the weight-average molecular weight Mw of the organic binder used as binder is determined by gel permeation chromatography (GPC) normalized with commonly used standards, i.e. polystyrene or polyethylene glycol / oxide (PEG / PEO) known to those skilled in the art.

[0043] According to a particularly preferred embodiment of the present invention, the organic binder is polyvinylpyrrolidone (PVP) having a weight average molecular weight Mw of about 10,000 to 5,000,000 g / mol, preferably about 10,000 to 1,000,000 g / mol, more preferably about 20,000 to 100,000 g / mol.

[0044] Suitable organic solvents that can be incorporated into the inks of the present invention are those that have a boiling point of at least 100° C. and in which the organic binder is soluble. Preferably, the organic solvent can be selected from the group consisting of toluene, ethylbenzene, chlorobenzene, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide, cyclohexanol, cyclohexanone, and mixtures thereof. In one particularly preferred embodiment, the organic solvent is N-methyl-2-pyrrolidone (NMP).

[0045] The mixing ratio of the organic binder in the organic solvent is not particularly limited and simply depends on the solubility of the organic binder in the particular solvent and / or the desired viscosity of the ink. In a preferred embodiment, the weight ratio of the organic binder to the organic solvent is, but is not limited to, 0.1:99.9 to 10:90.

[0046] The mixing ratio of the powders of the precursor material for the thermoelectric material and the precursor material for the inorganic binder to the solvent containing the organic binder is not particularly limited. In general, the weight ratio of the precursor material to the total weight of the organic binder and the organic solvent is in the range of 0.01:1 to 0.5:1.

[0047] According to a preferred embodiment of the present invention, the weight ratio of the inorganic binder precursor material containing Cu powder, Se powder and S powder to the total weight of the organic binder and the organic solvent is in the range of 0.5:1 to 5:1, more preferably 1:1 to 3:1.

[0048] As mentioned above, the ink composition according to the present invention may further comprise one or more additives, for example to control the viscosity and density of the ink. Preferably, the ink composition according to the present invention further comprises at least one additive selected from siliceous or aluminous materials and / or liquid rheological dispersion additives. Most preferably, the ink composition comprises fumed silica and BYK430. Of course, other additives may be incorporated into the ink composition to adjust other properties of the resulting TE material.

[0049] The amount of the additive may be in the range of 0.001 to 5.0% by weight based on the total weight of the ink composition.

[0050] Furthermore, the particle size of each of the Cu powder, Se powder, and S powder blended in the inorganic binder precursor material is not particularly limited and can be selected according to the desired application and / or commercial availability of the TE material. In general, suitable Cu powder, Se powder, and S powder have a particle size of 500 μm or less. Preferably, the particle size of the Cu powder, Se powder, and S powder is 150 μm or less, more preferably 10.0 μm or less, even more preferably 1.0 μm or less, and most preferably 500 nm or less.

[0051] Although there is no particular lower limit on the particle size, particularly for inkjet printable inks, the Cu, Se and S powders preferably have a particle size of at least 10 nm, more preferably at least 100 nm. The upper particle size limits for the Cu, Se and S powders refer to the maximum particle size of each powder, which is generally specified by manufacturer data or can be determined by laser diffraction analysis, particularly for small particles, or by sieve analysis, particularly for large particles.

[0052] If the precursor materials for the thermoelectric material are also in powder form, the particle size of each powder may be 150 μm or less, preferably 10.0 μm or less, more preferably 1.0 μm or less, and most preferably 500 nm or less. The lower particle size limit is not particularly limited. In particular for inkjet printable inks, the powders may have a particle size of at least 10 nm, more preferably at least 100 nm. The upper particle size limit refers to the maximum particle size of each powder, which is generally specified by the manufacturer's data or can be measured by laser diffraction analysis, especially for small particles, or by sieve analysis, especially for large particles.

[0053] The ink composition according to the present invention can be prepared by conventional mixing procedures. For example, but not limited to, the ink composition can be prepared by mixing the precursor material for inorganic binder, including a mixture of Cu powder, Se powder and S powder, the precursor material for thermoelectric material, organic solvent, organic binder and optional additives in a specific weight ratio using a magnetic stirrer. Of course, other mixing devices may be adopted to reduce particle size and obtain a homogeneous mixture of the aforementioned components. The mixing may be performed at room temperature (RT), i.e., about 20° C., or at a higher temperature. Usually, a homogeneous mixture of precursor materials is obtained after stirring for at least 5 minutes.

[0054] In a preferred embodiment, the ink can be prepared by wet ball milling the thermoelectric precursor material and the inorganic binder precursor material in the presence of an organic solvent and an organic binder. Surprisingly, it has been found that the printed thermoelectric material prepared from the wet ball milled ink exhibits significantly improved flexibility.

[0055] The ink composition is then printed onto a substrate to preferably form a thin film of the ink composition to produce a flexible printed TE material, and according to the present invention, the ink composition, preferably in the form of a thin film, is then sintered at a temperature of 200° C. to 500° C. for at least 60 seconds.

[0056] To provide a printed thin film, any method known in the art that allows coating of the ink composition on a substrate can be employed. Preferably, the printed thin film is formed by applying a screen printing method, a doctor blade coating method, an airbrush coating method or an inkjet printing method. These methods usually provide a two-dimensional (2D) layer of the ink composition. However, the present invention is not limited to a two-dimensional thin film, and the ink composition can also be used in a three-dimensional (3D) printing technique.

[0057] The substrate is not particularly limited, and commonly used substrates such as glass substrates and substrates for flexible integrated circuits can be used. However, the substrate is preferably flexible, and a thin polyethylene naphthalate (PEN) or polyethylene terephthalate (PET) film is most preferred.

[0058] After printing the ink composition on a substrate, the printed ink composition, preferably in the form of a thin film, is sintered at a temperature of 200°C to 500°C to react the precursor materials for the inorganic binder and form the desired thermoelectric material / inorganic binder composite. At a temperature of about 200°C, elemental Cu, Se, and S begin to react, and at about 350°C, Cu is converted to Cu by thermally stimulated dissociative adsorption of Se and S by Cu. 2 (S x Se 1-x ) phase was found to be formed.

[0059] According to the present invention, the sintering time is not particularly limited and depends on the sintering temperature. In general, it has been found that the higher the sintering temperature and the shorter the sintering time, the higher the TE performance. The sintering step is carried out for at least 60 seconds. The upper limit of the sintering time is preferably 20 minutes or less.

[0060] Sintering was performed under vacuum or with Ar, N 2 The sintering can be carried out in an inert atmosphere such as a sintering gas, a sintering gas atmosphere, etc. Furthermore, the sintering can be carried out once or multiple times.

[0061] According to the present invention, in order to reduce oxidation, a thin film of the ink composition can also be coated with, for example, a printable methylcellulose solution or any other suitable polymer solution during sintering.

[0062] In one particular embodiment, a method for producing a flexible printed thermoelectric material includes the steps of providing an ink composition by wet ball milling precursor materials for the TE material, precursor materials for the inorganic binder including Cu powder and Se powder, an organic solvent and an organic binder, printing the ink composition onto a flexible substrate, sintering the ink composition by photonic flash sintering, and pressing the printed TE material. In this particular embodiment, the TE material is preferably Bi. 0.5 Sb 1.5 Te 3 Thus, the precursor for the TE material comprises a powder of a Bi-Sb-Te alloy with a molar ratio of Te, Bi, and Sb of 3:0.5:1.5. This particular manufacturing method allows the flexible printed thermoelectric material to further improve the flexibility of the resulting printed TE material. However, it should be noted that the pressing step is not necessarily included in the manufacturing method of the present invention, and flexible printed TE materials with good properties can be obtained without any pressing step. Exemplary photonic flash sintering (pulse) conditions using a FulseForge light curing system (NOVACENTRIX) are as follows: Bank voltage: 320V Envelope: 5000μs μPulse: 35 Duty cycle: 50% Estimated temperature reached: 400~500℃

[0063] However, the parameters can be modified and adapted appropriately depending on the material and substrate used.

[0064] As mentioned above, the flexible printed TE material obtained by the method according to the present invention is a non-stoichiometric β-Cu2-δ S x Se 1-x phase, where 0≦x≦0.20 and 0≦δ≦0.15. In a preferred embodiment, the off-stoichiometry is 0.02≦δ≦0.10, more preferably 0.03≦δ≦0.10. Depending on the composition of the inorganic binder precursor material incorporated in the ink of the present invention, β-Cu 2-δ S x Se 1-x The sulfur-containing phase bridges the grains of the TE material, unlike conventional inorganic powder-based printed thin films that contain grain boundaries, minimizing the disruption of carrier transport at the grain boundaries caused by binders and additives, resulting in favorable high electrical conductivity σ and thus improved TE performance.

[0065] Therefore, the present invention provides, for example, 200 μVK -1 It has a very high Seebeck coefficient (S) exceeding 1500 μWm at room temperature. -1 K -2 In addition, as described in more detail in the Examples below, very high figures of merit exceeding 1.5 have been achieved.

[0066] According to the present invention it is possible to provide a flexible printed TE material on the micrometer scale. According to a preferred embodiment, the thickness of the flexible printed TE material is in the range of 10-250 μm.

[0067] By using the TE material according to the invention as the p-leg, a flexible printed TE generator can be provided. Thus, the invention further relates to a flexible printed thermoelectric generator (printed TEG) comprising a flexible printed thermoelectric material as the p-leg. In particular, the printed TEG according to the invention can comprise from a few to more than 1000 thermocouples using the flexible printed TE material as the p-leg.

[0068] According to a preferred embodiment, the printed TEG is made of n-type Bi 2 (TeSe) 3 The n-type legs are made from Ag-Se based ink compositions for thermoelectric inks or n-type printable thermoelectric materials. Such Ag-Se based ink compositions are described in EP 19198306.3.

[0069] The flexible printed TE material according to the present invention can be used in commercial applications of high power density flexible printed TEGs due to its high TE performance, reproducibility and stability. Flexible printed TEGs can have diverse applications in waste heat recovery devices for industrial applications, geothermal energy, energy harvesting for vehicles, body heat harvesters, and autonomous sensor systems such as heat flow sensors. Besides waste heat recovery applications, flexible printed devices can also be used for cooling applications. In particular, the printed TEG according to the present invention can be integrated with wearable materials such as helmets and clothing to maintain or reduce body temperature.

[0070] The present invention will be further illustrated by the following examples, which should not be construed as limiting the invention.

[0071] Working Example material: In the following examples, the following materials were used: p-type BST (Bi 0.5 Sb 1.5 Te 3 The materials used were: ingots of ZnO (beads, 99.99% on a trace metals basis, Sigma-Aldrich), copper powder (spherical) (10–25 μm, 98%, Sigma-Aldrich), Se powder (100 mesh, >99.5% on a trace metals basis, Sigma Aldrich), sulfur powder (Sigma-Aldrich), N-methyl-2-pyrrolidone (NMP) (dehydrated, 99.5%, Sigma-Aldrich), polyvinylpyrrolidone (PVP) (average Mw 40000, Sigma Aldrich), fumed silica (Evonik), polyethylene naphthalate (PEN), and Kapton substrates.

[0072] Characterization methods: Crystallographic and phase analyses of the printed thin films were performed by X-ray diffraction with Cu-Kα radiation on a BRUKER D8 diffractometer equipped with a Lynxeye XE detector of the Bragg-Brentano type and an Anton Paar HTK1200 heating chamber. Morphological and microstructural analyses were performed with a secondary electron microscope (SEM, FEI XL30S, PHILIPS). Elemental analyses were performed with an electron probe microanalyser (EPMA, JOEL). The thickness of the printed thin films was measured with a BRUKER 3D microscope based on white light interferometry (WLI). The transport parameters at room temperature (RT) of the thin films on glass substrates were determined using a Hall measurement setup (Linseis HCS 10). The Hall measurement technique (Linseis HCS 10) was used to measure the temperature-dependent transport parameters electrical conductivity (σ), Hall coefficient (R H ), Hall mobility (μ H ), carrier concentration (η H ) and the type of charge carriers were determined. The temperature-dependent bulk thermal conductivity (κ) of 10 mm disks fabricated with (1-y)BST-(y) inorganic binder ink by cold pressing at a pressure of 50 MPa followed by sintering at 703 K in vacuum for 10 min was measured using a Netzsch LFA-427. The Seebeck coefficient S at RT and the temperature-dependent Seebeck coefficient S in the temperature range of 300–373 K of the printed thin films were measured using a custom-built setup with an experimental measurement error of about 10%. The Seebeck measurement setup uses two temperature-controlled copper blocks in close proximity that generate a temperature difference. The sample is placed across the two blocks and two temperature sensors are pressed against the sample to measure the temperature on both sides of the sample. The Seebeck voltage is measured between these two tips so that thermal and electrical measurements are performed at the same location on the sample. The thermal conductivity (κ) of the printed thin films was measured using a Linseis Thin Film Analysis (TFA) system.

[0073] Example 1: Non-stoichiometric β-Cu 2-δp-type Bis(II) with high figure of merit at room temperature containing Se-based inorganic binder (IB) 0.5 Sb 1.5 Te 3 (BST)-based printable TE materials First, to prepare a Cu-Se-based inorganic binder, powder elements (Cu and Se) were weighed out in a stoichiometric ratio. Next, these powders were mixed with an organic solvent-PVP solution (organic solvent NMP:binder (PVP) = 93:7) and fumed silica in a ratio of 60:40:0.5. The resulting mixture was stirred at 1000 rpm for 12 hours. p-type Bi 0.5 Sb 1.5 Te 3 (BST) was ground in a mortar and pestle for 20 min to obtain powders with sizes less than 100 μm. The resulting powder was mixed with Cu-Se based inorganic binder (IB) in various ratios of (1-y)BST:(y)IB (y=0-100) and its performance was optimized by evaluating its morphological and physical properties. Then, 20 wt% of organic solvent-PVP solution was further added to this mixture. The final mixture was then stirred at 1000 rpm for 2 h at room temperature.

[0074] The prepared ink was applied / printed onto each substrate (glass and Kapton) using a doctor blade coating technique. Finally, the printed thin film with a thickness of about 150-200 μm was sintered in a vacuum oven at 703 K for 10 min, cooled to below 350 K, and then removed.

[0075] Crystallographic and microstructural analyses The crystal structures of the printed thin films of (1-y)BST-(y)IB with y = 0, y = 0.10 and y = 1 sintered at 703 K were obtained by XRD analysis at room temperature (see Figure 1). The XRD pattern of the thin film with y = 0 corresponds to the original p-type Bi 0.5 Sb 1.5 Te 3 The XRD pattern of the thin film at y=0.05 corresponds to the pattern of the material. 0.5 Sb 1.5 Te 3 Phase together with β-Cu 2-δIt shows that the Se phase is formed. The XRD pattern at RT of the pure inorganic binder thin film (y = 1) is a non-stoichiometric cubic β-Cu with a small amount of excess Cu 2-δ Se phase is prominent. However, it was found that the amount of excess Cu is small (<1 vol%).

[0076] Cu 2 To investigate the formation temperature of the Cu 2 Se phase, temperature-dependent XRD analysis of the printed thin film with y = 1 was performed at 298 - 673 K (see Fig. 1d). The thin film with y = 1 was found to be a mixture of unreacted Cu and Se at room temperature. At temperatures above 473 K, single Cu and Se began to react, and Cu 2 2 Se phase was found to be formed by the thermally stimulated desorption adsorption of Se by Cu at 623 K.

[0077] As a result, in the printed thin film with 0 < y ≤ 0.20, the BST TE crystallites are bonded by the highly conductive Cu 2 2 Se phase, minimizing the interfacial resistance at the grain boundaries. The detailed crystal structure of the Cu 2 2 Se phase at room temperature was obtained by performing Rietveld refinement of the XRD pattern of the thin film with y = 1 using the FULLPROF program. The crystal structure and refinement results are shown in Fig. 1(b).

[0078] From the Rietveld refinement analysis, the thin film with y = 1 corresponds to the main non-stoichiometric cubic β-Cu 2-δ 2-δ Se phase belonging to the space group Fm-3m, and it was found that the excess Cu is less than 1 vol%. The non-stoichiometry "δ" was found to be in the range of 0.03 - 0.04. Overall, Cu 2 2 Se is found to be the α-Cu 2 2 Se phase with a complex structure at room temperature, but due to non-stoichiometry, the formation of the cubic β-Cu 2-δ 2-δ Se phase can occur.

[0079] The non-stoichiometry with δ = 0.03 is the cubic β-Cu 2 2It is known that this induces a structural phase transition to the Se phase. Therefore, in this embodiment, 2-δ Since nonstoichiometry δ was observed in Se, cubic β-Cu 2 The Se phase is formed. β-Cu 2-δ The lattice constant of the unit cell of the Se phase was calculated to be a = 0.576(2) nm. 2-δ The Se atoms in the Se crystal lattice are found to occupy Wyckoff positions 4a (0,0,0) in a face-centered cubic arrangement, while the disordered Cu atoms are located at two distinct Wyckoff positions 8c (1 / 4,1 / 4,1 / 4) and 32f (x,x,x).

[0080] Figure 1(c) shows the β-Cu phase along the

[0001] direction at z / c=0, z / c=0.25, and z / c=0.5. 2-δ Fourier maps of the electron density distribution in the unit cell of Se are shown. It can be seen that the electron density distribution of Se atoms in the z / c=0 plane is concentrated at the vertices and the center 4a(0,0,0) positions. Similarly, from the Fourier maps of the atomic electron density distribution in the z / c=0.25 and z / c=0.5 planes, the positions of Cu and Se atoms can be located at 8c(1 / 4,1 / 4,1 / 4) and 4a(0,0,0). The morphology of the printed thin film at y=0.10 sintered at 703K was analyzed by white light interferometry and found to be homogeneous.

[0081] Thermoelectric performance of printed thin films The composition-dependent Seebeck coefficient of printed thin films with varying contents of Cu-Se-based inorganic binder IB sintered at 623 K and 703 K was investigated to identify the optimal composition and sintering temperature (see Fig. 2(a)). Thin films containing less than 20 wt% IB exhibited a Seebeck coefficient of 100 μVK. -1 The thin films containing more than 20 wt.% IB exhibited Seebeck coefficients S of more than 1000 μm and, except for the parent compound, were found to have moderately high electrical conductivity. The low Seebeck coefficients S of the thin films containing more than 20 wt.% IB were due to the low 2 This indicates the formation of a percolation pathway for the Se phase.

[0082] Therefore, detailed temperature-dependent thermal conductivity characteristics were investigated in the temperature range of 300K to 400K for a printed thin film on a glass substrate with less than 20% by weight of inorganic binder IB and a thin film with 100% by weight of IB. H ) calculated from the hole carrier concentration (η H ) and Hall carrier mobility (μ H The change in Cu with temperature is shown in Figures 2(c) and (d). The transport parameters of the printed thin films at room temperature are listed in Table 1. 2 The amount of Se phase formed increases and its respective carrier concentration increases, so the η H increases. η H is 2 x 10 19 cm -3 ~5×10 20 cm -3 was found to be in the range of

[0083] [Table 1]

[0084] Temperature-dependent η H The change in μ was found to be small for all films except for the film with y = 1. Presumably, the Cu ions become more disordered, which enhances the ionic conductivity of the film with y = 1 and increases the overall carrier concentration at high temperatures. On the other hand, μ H At y=0.05, the initial distance is about 47cm. 2 V -1 s -1 and decreases with increasing content of inorganic binder IB. For all films except y=0, μ H is the temperature dependent η H decreases with increasing temperature due to the formation of disordered Cu ions, which coincides with

[0085] The temperature dependent TE parameters in the range of 300K-400K for the thin films (1-y)BST-(y)IB with y=0, y=0.10 and y=1 are shown in Figure 3. The sign of the Seebeck coefficient value S is found to be positive for all the thin films, indicating that the majority of the charge carriers are p-type, and the pristine thin film at y=0 exhibits the highest Seebeck coefficient value S over the entire temperature range, about 240 μVK at room temperature. -1 The Seebeck coefficient S increases with increasing temperature and reaches a maximum value at about 360 K for all BST-based thin films (see Fig. 3(a)).

[0086] The pristine thin film at y = 0 exhibits semiconducting behavior. However, the electrical conductivity σ of the inorganic printed thin film is 400 Scm at room temperature. -1 It is found that the charge transport in all thin films containing inorganic binder IB is greater than 0.01, and decreases with increasing temperature due to the reduced carrier mobility in the thin films containing inorganic binder IB (see Fig. 3(b)). The metallic behavior of the thin films indicates that the charge transport in all thin films containing inorganic binder is similar to that of highly conductive β-Cu even below the percolation threshold. 2 The thermal conductivity κ of all thin films decreases slightly with increasing temperature and is estimated to be low compared to its bulk value thermal conductivity κ. The low κ value is mainly due to the low density of the thin films (less than 60% of the theoretical density) and the reduced thermal conduction in the presence of the remaining organic binders and additives. At y=0 it is about 0.30 Wm -1 K -1 The lowest κ of 0.65 Wm was observed, which increased with increasing inorganic binder content at RT, and was approximately 0.65 Wm for the sample with y = 1. -1 K -1 It reaches a maximum value of κ (see Fig. 3(c)). The lattice contribution to the thermal conductivity κ is dominant for the thin film at y = 0, while the contribution from electronic transport is negligibly small. The prominence of the electronic contribution to the thermal conductivity κ is found to increase with increasing content of inorganic binder in the composition, thus increasing the total thermal conductivity. The temperature-dependent power factor S for all thin films calculated using S and σ 2 σ is shown in Fig. 3(d). At y = 0.05, it is about 18 μW cm at room temperature.-1 K -2 The highest power factor value was observed for y = 0.10, which is approximately 20 μW cm at 360 K. -1 K -2 reaches a maximum value of

[0087] However, it was found that compositions with inorganic binder contents between 5 and 10 wt% could show improved power factors. From the power factor and thermal conductivity values ​​of all the films, the temperature-dependent figure of merit ZT was estimated (see Figure 4). ZT was found to increase with increasing temperature for all the films. The films with y=0.05 showed a high ZT of about 1.2 at room temperature, which increases with increasing temperature. The films with y=0.05 and y=0.10 showed maximum ZT of more than 1.5 at temperatures T>350 K, which is very high for pressureless processed printed TE films.

[0088] Performance of printed thermoelectric generator (printed TEG) First, to fabricate the p-type legs of the printed TEG, four thin films with a size of approximately 4 cm × 0.5 cm were printed on a Kapton substrate using a prepared printing ink containing 10 wt% inorganic binder IB. The Kapton substrate was rubbed with emery paper to roughen the surface and improve the adhesion of the thin films. These thin films were then sintered at 703 K for 10 min. These thin films were electrically coupled in series and thermally in parallel with silver ink to fabricate a TE power generator (printed TEG). The printed TEG was characterized by the maximum power point tracking method, with the device current varied from 0 to 500 μA and the temperature difference ΔT varied from 10 to 40 K. The output voltage of the printed TEG was measured with a KEITHLEY source measurement unit 2601B. At that time, one side of the printed TEG was thermally coupled to the high temperature unit of the measurement setup, and the other side of the device was exposed to a normal environment. The performance of the printed TEG with varying current is shown in Figure 5. At ΔT=40K, the printed TEG achieves an open circuit voltage of 14mV and a maximum power output of 1.7μW.

[0089] Example 2: Flexible Cu for large area device applications 2Se-based inorganic printed thermoelectric thin films Synthesis of TE inks and thin films: S-doped Cu 2 Se 1-x S x The printable TE materials based on the system were prepared with 0≦x≦0.2 using ball milling. First, powder elements Cu, Se and S were weighed in a stoichiometric ratio. Then, these elements were mixed with 30% by weight of an organic solvent containing PVP as an organic binder and NMP as a solvent in a ratio of 6:94. The mixture was placed in a 120 ml zirconia jar containing 10 mm zirconia balls. The weight ratio of the balls to the mixture was 10:1. The mixture was then ground in a wet milling process using a Fritsch Planetary Mill PULVERISETTE 5 premium line. Each composition was milled at 200 rpm for each milling time ranging from 10 min to 300 min. The resulting ink was printed on a substrate and sintered in a vacuum oven at 623 K for 10 min. The sintered thin film was removed from the vacuum oven after cooling to below 373 K.

[0090] Structural, morphological and mechanical characterization Cu 2 Se 1-x S x The structural and phase analysis of the thin films was carried out at room temperature after sintering using XRD (see Figures 6(a) and 6(b)). The XRD patterns of the printed thin films with x = 0 and x = 0.10 sintered at 623 K show that the cubic β-Cu phase at RT is 2-δ This indicates that a Se phase is formed. It was also found that a small amount of unreacted Cu exists in the thin film. Cu 2 To analyze the crystal structure of the Se phase and its change with S substitution, Rietveld refinement was performed on the XRD patterns at RT of the thin films with x = 0 and x = 0.10 using the FULLPROF program. 2 Rietveld refinement of the XRD pattern of the Se thin film reveals that the space group

number

[0001] direction. 2-δ Se 0.9 S 0.1 The electron density distribution in the cubic unit cell of can be visualized at 4a (0,0,0) and 8c (1 / 4,1 / 4,1 / 4) in the Fourier maps (see the inset in Fig. 6(b)).

[0091] Cu at x=0.10 2 Se 1-x S x To confirm the mechanical flexibility of the thin film, the resistance (R o The change in the internal resistance (△R×100 / R) was investigated (see Fig. 7(b) and Fig. 7(c)). Even when the thin film was repeatedly bent up to 90°, the internal resistance (△R×100 / R o ) did not show any significant change. The resistance of the thin film increased from 24 Ω to 35 Ω after 100 bending cycles, and △R×100 / R owas found to be less than 30% after 100 bending cycles (see Fig. 7(b)). The resistance of the thin film with bending cycles under bending and stretching conditions is shown in Fig. 7(c).

[0092] The Seebeck coefficient of the original printed thin film at x = 0 is about 20 μVK at room temperature. -1 By replacing Se with isoelectronic S up to 20 atomic %, the Seebeck coefficient was reduced to 40 μVK. -1 At the same time, the carrier concentration value is increased by a factor of 10 compared to the original thin film. 22 cm -3 from values ​​of the order of 10 for S-doped thin films. 21 cm -3 The decrease in the eigenvalues ​​decreases to values ​​of the order of .

[0093] The 4p level of the Se atom and the 3p level of the S atom are in similar energy states, leading to band convergence. As a result, the effective mass increases and the carrier mobility decreases, which leads to an increase in the Seebeck coefficient value. At x=0, it is about 7 cm. 2 V -1 s -1 The carrier mobility, which was previously 5 cm for the thin film with x>0, 2 V -1 s -1 It was found that the concentration of

[0094] The Seebeck coefficient of the material is affected by the ball milling process performed during the preparation of the ink. Little change is observed below 10% doping. The Seebeck coefficient starts to decrease with milling time, reaching an optimum value of 55 μVK after 30 minutes of milling. -1 Therefore, when milling was performed for 5 hours, the -1 However, this trend changes with increasing doping. With 20% S, the Seebeck coefficient, after an initial decay with milling time, begins to increase again with further milling. However, the maximum Seebeck coefficient can be achieved after 30 minutes of ball milling at doping levels of 10% or less.

[0095] Hall measurements revealed that the electrical conductivity changes linearly with temperature, since as the temperature increases, the number of charge carriers flowing through the compound also increases. Analysis of the ink milled for 30 min with 10% doping revealed a notable 22% increase in electrical conductivity when the temperature was increased from 298 K to 363 K, as shown in Figure 8(b). 2 Since Se exhibits semiconducting properties with temperature, the carrier concentration is expected to increase. From Fig. 8(c), it is clear that the hole carrier concentration follows the expected pattern. On the other hand, the increase in the energy of the charge carriers at high temperatures increases the number of collisions, which reduces the carrier mobility. However, the Cu concentration shown in Fig. 8(d) 2 In the experimental Se samples, almost no change in carrier mobility is observed.

[0096] Original Printed Cu 2 Cu doped with Se and 10 at.% S 2 The temperature-dependent TE performance of Se is shown in Figure 9. The Seebeck coefficient is not strongly affected by temperature. From 300K to 375K, almost no significant change in the Seebeck coefficient is observed. 2 The electrical conductivity of Se varies inversely with temperature, whereas the opposite change is observed when it is doped with S (see Figure 5(b)). Figure 5(c) shows that the incremental change in thermal conductivity with increasing temperature is minimal. Overall, stable thermoelectric properties are observed with little deviation upon manipulation of temperature. As a result, the power factor and ZT values ​​also vary little over the investigated temperature range, as shown in Figure 5(d) and Figure 5(e). At room temperature, the thermal conductivity is 250 μW cm -1 K -2 and ZT values ​​of 0.15 are achieved. The figure of merit ZT is found to increase to 0.21 at 375K.

[0097] Referring to FIG. 10, S-doped printed Cu 2 Se is used as the p-type leg, and printed Ag 2The performance of a four-legged TE device (flex TEG) where Se is used as the n-type material has been measured. The VI curves shown in Figure 10(a) show a stable linear relationship. The maximum power of 0.35 μW is achieved at a temperature difference of 45 K between the hot and cold ends and an open circuit voltage Voc of 12 mV. From Figure 6(c), it can be seen that there is a linear proportional relationship between the power output and the open circuit voltage as the temperature changes. As seen in Figure 10(d), the Seebeck coefficient of the thermocouple reaches a peak value of 190 μVK at a low temperature difference of 5 K. -1 was achieved, but 140μVK -1 It shows a stable value around this range.

[0098] As demonstrated above, it is possible to fabricate nonstoichiometric β-Cu via a simple printing-sintering process. 2-δ A 2D / 3D printable TE material with a high figure of merit at room temperature was developed by bridging the TE grains using a Se-based inorganic binder (IB). 0.5 Sb 1.5 Te 3 (BST) printed material is 200μVK at room temperature -1 Seebeck coefficient (S) exceeding 1500 μWm -1 K -2 A very high TE power factor exceeding 10 ...

Claims

1. An ink composition for a printable thermoelectric material, the ink composition comprising: A precursor material for a thermoelectric material; A precursor material for an inorganic binder comprising a mixture of Cu powder, Se powder and S powder; An organic binder; Organic solvent The molar ratio of the Cu powder to the sum of the Se powder and the S powder is 2:1, and the molar ratio of the Se powder to the S powder represented by the formula (1-x)Se:xS is in the range of 0≦x≦0.20; the weight ratio of the precursor material for the thermoelectric material to the precursor material for the inorganic binder, expressed as [(1-y) thermoelectric material:y inorganic binder], is in the range of 0<y≦0.

25.

2. The ink composition according to claim 1 , wherein the precursor material for a thermoelectric material is a precursor material for a p-type thermoelectric material.

3. 3. The ink composition according to claim 2, wherein the precursor material for the p-type thermoelectric material is a powder of a Bi-Sb-Te alloy in which the molar ratio of Te, Bi and Sb is 3:0.5:1.

5.

4. The ink composition of claim 1 further comprising a siliceous or aluminous material.

5. The ink composition according to claim 1 , wherein the particle size of each of the Cu powder, the Se powder and the S powder is 500 μm or less.

6. 6. The ink composition according to claim 1, wherein a weight ratio of the precursor material for the thermoelectric material to the precursor material for the inorganic binder, expressed as [(1-y) thermoelectric material:y inorganic binder], is in the range of 0.05≦y≦0.

10.

7. A Cu—Se—S based ink composition for a printable thermoelectric material, the ink composition comprising: A mixture of Cu powder, Se powder and S powder; An organic binder; Organic solvent wherein a molar ratio of the Cu powder to the combined total of the Se powder and the S powder is 2:1, and a molar ratio of the Se powder to the S powder represented by the formula (1-x)Se:xS is in the range of 0<x≦0.

20.

8. A method for manufacturing a flexible printed thermoelectric material, comprising the steps of: - providing an ink composition according to any one of claims 1 to 6; - printing said ink composition onto a substrate; - sintering the ink composition at a temperature between 200°C and 500°C for at least 60 seconds; A method comprising:

9. The method of claim 8 , wherein the step of sintering the ink composition is performed by photonic flash sintering of the ink composition and pressing the printed film after sintering.

10. The method of claim 8 or 9, wherein the step of providing the ink composition comprises wet ball milling the precursor material for the thermoelectric material, the precursor material for the inorganic binder, the organic binder and the organic solvent.

11. A method for manufacturing a flexible printed thermoelectric material, comprising the steps of: - providing an ink composition according to claim 7; - printing said ink composition onto a substrate; - sintering the ink composition at a temperature between 200°C and 500°C for at least 60 seconds; A method comprising:

12. The method of claim 11, wherein the step of sintering the ink composition is performed by photonic flash sintering of the ink composition, and pressing the printed thin film after sintering.

13. 13. The method of claim 8, wherein the step of printing the ink composition onto a substrate is carried out by at least one selected from the group consisting of screen printing, doctor blade coating, airbrush painting, inkjet printing and 3D printing.

14. A flexible printed thermoelectric material obtained by sintering the ink composition according to any one of claims 1 to 7 onto a substrate, the printed thermoelectric material comprising: Cu 2-δ S x Se 1-x phase, where 0≦x≦0.20 and 0≦δ≦0.

15.

15. The flexible printed thermoelectric material of claim 14 having a thickness of 10 to 250 μm.

16. 16. A flexible printed thermoelectric generator comprising the printed thermoelectric material of claim 14 or 15 as a p-type leg.

17. 20. The flexible printed thermoelectric generator of claim 16, further comprising an n-type leg fabricated from a Ag-Se based ink composition for n-type printable thermoelectric materials.

18. 18. Use of the printed thermoelectric generator of claim 16 or 17 in waste heat recovery applications or in cooling applications integrated with wearable materials to maintain or reduce body temperature.

Citation Information

Patent Citations

  • Ag-se-based n-type thermoelectric material and flexible printed thermoelectric generator comprising the same

    EP3796404A1

  • Method of manufacturing thermoelectric conversion element

    JP2013251333A

  • Manufacturing method of thermoelectric conversion element and thermoelectric conversion element

    JP2020043191A

  • Thermoelectric material ink, thermoelectric element and thermoelectric device manufactured using the thermoelectric material ink, and method of manufacturing the thermoelectric device

    US20190035996A1